Kv8.1, a new neuronal potassium channel subunit with specific inhibitory properties towards Shab and Shaw channels. - Hugnot, J P (1996)
Outward rectifier K+ channels have a characteristic structure with six transmembrane segments and one pore region. A new member of this family of transmembrane proteins has been cloned and called Kv8.1. Kv8.1 is essentially present in the brain where it is located mainly in layers II, IV and VI of the cerebral cortex, in hippocampus, in CA1-CA4 pyramidal cell layer as well in granule cells of the dentate gyrus, in the granule cell layer and in the Purkinje cell layer of the cerebellum. The Kv8.1 gene is in the 8q22.3-8q24.1 region of the human genome. Although Kv8.1 has the hallmarks of functional subunits of outward rectifier K+ channels, injection of its cRNA in Xenopus oocytes does not produce K+ currents. However Kv8.1 abolishes the functional expression of members of the Kv2 and Kv3 subfamilies, suggesting that the functional role of Kv8.1 might be to inhibit the function of a particular class of outward rectifier K+ channel types. Immunoprecipitation studies have demonstrated that inhibition occurs by formation of heteropolymeric channels, and results obtained with Kv8.1 chimeras have indicated that association of Kv8.1 with other types of subunits is via its N-terminal domain.